"Severing the Connections in a Complex Community": The Grange, Patrons of Industry and the Construction/Contestation of a Late 19th-century Agrarian Identity in Ontario - Ferry, Darren (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2004)
Abstract The leadership of the Patrons of Husbandry and the Patrons of Industry in late 19th-century Ontario offered ideological visions of class harmony, the promise of united political action through antipartyism, and the assurance of material prosperity to Ontario's farmers, the history of agrarian protest can be viewed as one of broken promises and unfulfilled expectations. The tensions inherent in the differing material circumstances and various representational philosophies of agriculture made it impossible for the Dominion Grange and the Patrons of Industry to sustain harmony and unity for any length of time within a deeply divided agricultural population. As a result, entrenched ideological differences regarding the merits or shortcomings of the co-operative principle in the Dominion Grange and Patrons of Industry would highlight the tensions and conflicts intrinsic to the varied approaches of the farmers themselves. And yet the initial success of both agrarian protest movements in Ontario displayed at least a willingness on the part of farmers to bond together for united action. Their cataclysmic collapse into irrelevancy by the turn of the century, however, also revealed the ideological, cultural, social, and economic fissures situated within Ontario's rural populace.